2020
DOI: 10.24818/jamis.2020.01007
|View full text |Cite
|
Sign up to set email alerts
|

New coordinates of accounting academic education. A Romanian insight

Abstract: Research question: Are accounting graduates prepared to face IT developments in their profession? Motivation: The accounting profession is facing a rapid transformation involving digital technology that implies significant changes. "Modern accountants are expected to have a high level of IT knowledge and skills and towards that direction the curriculum in accounting education have to adopt a wide range of modules in order to provide accounting students with the required competencies" (El-Damarleh, 2017: 202). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It is very difficult protecting the anonymity of learners on the social network site (Melnikova, 2018). In the same vein, Stanciu et al (2012) found that the absence of personal data security policies may leave learners exposed to hackers, spam, malware, and phishing among Romanian learners, following the administration of a survey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is very difficult protecting the anonymity of learners on the social network site (Melnikova, 2018). In the same vein, Stanciu et al (2012) found that the absence of personal data security policies may leave learners exposed to hackers, spam, malware, and phishing among Romanian learners, following the administration of a survey.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Singapore Management University and USC Marshall School of Business offered master's degree programs in Data Analytics and Accounting whereas St. Mary's University (Texas, USA) offered a bachelor's degree program in Accounting and Data Analytics with courses such as accounting, data analytics, information systems management and quantitative management while the University of Pittsburgh offered a master's degree program in Accounting and Business Analytics (Stanciu et al, 2020). Furthermore, there is a wide variety of studies that focus on developing curricula and different teaching strategies or exercises with suggestions on how universities or courses might address accreditation requirements for the prevalence of this situation (Wang, 2021;Lawson at al., 2014;Buchheit et al, 2018).…”
Section: Integration Of Digital Technologies Into Accounting Curriculummentioning
confidence: 99%
“…Universities and accounting courses have recently accelerated their efforts to incorporate technology into their curricula (Qasım & Kharbat, 2020). In the study conducted with a random sample of 103 business schools from 50 states in the USA, Wang (2021) (Stanciu et al, 2020). Furthermore, there is a wide variety of studies that focus on developing curricula and different teaching strategies or exercises with suggestions on how universities or courses might address accreditation requirements for the prevalence of this situation (Wang, 2021;Lawson at al., 2014;Buchheit et al, 2018).…”
Section: Integration Of Digital Technologies Into Accounting Curriculummentioning
confidence: 99%